PERAN KOMUNIKASI KELUARGA DALAM MENGATASI â€œTOXIC PARENTSâ€ BAGI KESEHATAN MENTAL ANAK - Saskara, I Putu Adi; SM, Ulio (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The role of the family, especially parents, is very important for the formation of children's character, especially if the character building of children starts at an early age. Family communication is communication that occurs in a family, which is a way for a family member to interact with other members, as well as a forum for forming and developing the values needed as a guide for life. So that children can live their lives while in the community, what happens if a family communication pattern and the behavior of toxic parents mingle in a family will certainly affect the child's development and even the child's health. Poor mental health during childhood can lead to more serious behavioral disorders due to mental and emotional imbalances, as well as poor social life. For that, in communicating with children, mothers and fathers must pay attention to the character of the child, so that communication is effective. Communication must be established as early as possible and based on understanding from the mother-father. Of course, communication that can be carried out is not only limited to conversation, but can also be realized through actions, such as touching, caressing, kissing, caring, and positive words. This research is expected to have a positive effect on parents in choosing parenting styles. In addition, it can provide solutions to overcome toxic parents' behavior